Case Report: Evolution of a Severe Vascular Refractory Form of ECD Requiring Liver Transplantation Correlated With the Change in the Monocyte Subset Analysis - Razanamahery, Jérôme; Roggy, Anne; Emile, Jean-François; Malakhia, Alexandre; Lakkis, Zaher; Garnache-Ottou, Francine; Soumagne, Thibaud; Cohen-Aubart, Fleur; Haroche, Julien; Bonnotte, Bernard (Frontiers in Immunology, 2021)
Erdheim Chester disease is a rare histiocytosis characterized by iconic features associated with compatible histology. Most patients have somatic mutations in the MAP-kinase pathway gene, and the mutations occur in CD14+ monocytes. Differentiation of the myeloid lineage plays a central role in the pathogenesis of histiocytosis. Monocytes are myeloid-derived white blood cells, divided into three subsets, but only the CD14++CD16- "classical monocyte" can differentiate into dendritic cells and tissue macrophages. Since most mutations occur in CD14+ cells and since ECD patients have a particular monocytic phenotype resembling CMML, we studied the correlation between disease activity and monocytic subset distribution during the course of a severe vascular form of ECD requiring liver transplantation. During early follow-up, increased CD14++CD16- "classical monocyte" associated with decreased CD14lowCD16++ "non-classical monocyte" correlated with disease activity. Further studies are needed to confirm the use of monocyte as a marker of disease activity in patients with ECD.